Perbandingan Motivasi dan Hasil Belajar Siswa Antar SMA di Kota Medan pada Pelajaran Pendidikan Agama Islam - Mahyuddin Siregar; Yusnaili Budianti; Nurussakinah Daulay (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Student motivation is one of the factors that affect student learning outcomes, and will not be separated from the environment that supports learning activities in students. The background where students live can also affect their learning motivation and learning outcomes. The purpose of this study was to analyze and test hypotheses regarding the differences in learning motivation and learning outcomes of students at Al-Ulum Private High School Medan and Private Nurul Islam Indonesia High School Medan. The hypotheses of this study include: 1) There are differences in the learning motivation of students at the Al-Ulum Private High School Medan and the Private Nurul Islam Indonesia Senior High School Medan in the subject of Islamic Religious Education. 2) There are differences in student learning outcomes of Al-Ulum Private Senior High School Medan with Private Nurul Islam Indonesia High School Medan in Islamic Religious Education subjects. The method used in this study is a descriptive method with a comparative technique with a quantitative approach. The population of this study were all students of Al-Ulum Private High School Medan and Private High School Nurul Islam Indonesia Medan class XI for the academic year 2021-2022. The sample size is 86 students, with the sampling technique used is quota sampling. The research instrument used is a student learning motivation questionnaire with 45 questions that have been tested for validity and reliability; and documentation of student learning outcomes obtained from students' daily test scores; Data analysis used Independent Sample T-Test. The conclusions obtained from the results of this study are: 1) The learning motivation of Al-Ulum Medan Private High School students is better than the learning motivation of Indonesian Nurul Islam Private High School students, it is shown by the Al-Ulum Private High School Medan students are more active in learning Religious Education Islam compared to the students of the Indonesian Nurul Islam Private High School. This is evidenced by the average value of the learning motivation of the private high school students of Al-Ulum Medan of 93.12 while the learning motivation of the students of the private high school of Nurul Islam Indonesia is 83.72. 2) The learning outcomes of the private high school students of Al-Ulum Medan have similarities with the learning outcomes of the private high school students of Nurul Islam Indonesia. This is evidenced by the average value of student learning outcomes of Al-Ulum Private High School Medan of 87.34 while the learning outcomes of Indonesian Nurul Islam Private High School students of 85.89. 3) There is a significant difference in student learning motivation in Islamic Religious Education subjects between Al-Ulum Private High School students and Nurul Islam Indonesian Private High School students with a significance level of 0.006. 4) There is no significant difference in student learning outcomes in Islamic Religious Education subjects between Al-Ulum Private High School students and Nurul Islam Indonesian Private High School students with a significance level of 0.428.